Top‐Down CO Emissions Based On IASI Observations and Hemispheric Constraints on OH Levels - J.‐F. Müller; T. Stavrakou; M. Bauwens; M. George; D. Hurtmans; P.‐F. Coheur; C. Clerbaux; C. Sweeney (Geophysical Research Letters)
Abstract Assessments of carbon monoxide emissions through inverse modeling are dependent on the modeled abundance of the hydroxyl radical (OH) which controls both the primary sink of CO and its photochemical source through hydrocarbon oxidation. However, most chemistry transport models (CTMs) fall short of reproducing constraints on hemispherically averaged OH levels derived from methylchloroform (MCF) observations. Here we construct five different OH fields compatible with MCF‐based analyses, and we prescribe those fields in a global CTM to infer CO fluxes based on Infrared Atmospheric Sounding Interferometer (IASI) CO columns. Each OH field leads to a different set of optimized emissions. Comparisons with independent data (surface, ground‐based remotely sensed, aircraft) indicate that the inversion adopting the lowest average OH level in the Northern Hemisphere (7.8 × 105 molec cm−3, ∼18% lower than the best estimate based on MCF measurements) provides the best overall agreement with all tested observation data sets.